Optically stimulated luminescence dating of late Quaternary loess deposits in the coastal region of North China: Provenance and paleoclimatic implications. (15th August 2019) - Tian, Shengchen; Sun, Jimin; Lü, Lixing; Cao, Mengmeng; Zhang, Zhiliang; Lü, Tongyan
Abstract: The aeolian deposits in the coastal region of North China are important for reconstructing paleoclimate. In this paper, chronology, climatic proxies and chemical compositions of four loess sections were studied. Optically stimulated luminescence (OSL) dating results indicate that the coastal loess was accumulated during late Quaternary, with ages ranging from the penultimate glacial period to the latest Holocene. Both granulometric characteristics and geochemical properties indicate that the dust provenance of the coastal loess is partially different from that of the Chinese Loess Plateau, characterized by more proximal contributions. Except distal dust transported by northwesterly winter winds from the inland gobi and sand deserts, the coastal loess also contains proximal, local coarse particles, which were derived from the exposed shelf as well as neighboring hills. Multiple climatic proxies, including color, magnetic susceptibility and particle size parameters, correlate well with the marine SPECMAP δ 18 O record, indicating that climatic changes in the coastal region of North China during the late Quaternary was mainly controlled by variations of the East Asian monsoon, driven by changes in global ice volumes. Highlights: Luminescence dating of coastal loess in eastern North China. Coastal loess contain both distal and proximal source materials. Exposed shelf during glacial time serving as an important source for coastal loess. Costal loess reflects orbital climatic fluctuations driven by East Asian monsoon.